2021
DOI: 10.20944/preprints202106.0672.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Pharmaceuticals in Wastewater Treatment Plants: A Systematic Review on the Substances of Greatest Concern Responsible for the Development of Antimicrobial Resistance

Abstract: In recent years, there is a growing concern about the alarming spread of antimicrobial resistance (AMR) in different environments. Increasingly, many species of bacteria, fungi and viruses are becoming immune to the most commonly used pharmaceuticals. One of the causes of the development of the resistance is the persistence of these drugs, excreted by humans, in municipal and hospital wastewater (WW). Consequently, wastewater treatment plants (WWTPs) are a primary source of antimicrobial resistance genes as no… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 40 publications
(109 reference statements)
0
5
0
2
Order By: Relevance
“…Pharmaceuticals, even though with varying chemical structures are commonly intended to be active and persistent. Pharmaceuticals are transported via hospital and municipal wastewater to wastewater treatment plants (WWTP), which have been identified as the primary source for the increase in antimicrobial resistance genes (Frascaroli et al, 2021). Some of the pharmaceuticals do not alter their chemical composition upon consumption, and not all are removed in WWTPs.…”
Section: Fungal Degradation Of Pharmaceuticals and Personal Care Prod...mentioning
confidence: 99%
“…Pharmaceuticals, even though with varying chemical structures are commonly intended to be active and persistent. Pharmaceuticals are transported via hospital and municipal wastewater to wastewater treatment plants (WWTP), which have been identified as the primary source for the increase in antimicrobial resistance genes (Frascaroli et al, 2021). Some of the pharmaceuticals do not alter their chemical composition upon consumption, and not all are removed in WWTPs.…”
Section: Fungal Degradation Of Pharmaceuticals and Personal Care Prod...mentioning
confidence: 99%
“…When administrated, antibiotics are not completely metabolised, and via excreta, residual fractions and their metabolites reach local wastewater treatment plants (WWTPs) (Kümmerer et al, 2003b), where they may remain active (Roberts and Thomas, 2006). High concentrations of antibiotics, not removed by standard treatment approaches, have been identi ed in several studies of e uent wastewater (WW) released directly in aquatic environments (Frascaroli et al, 2021). After discharge into rivers, lakes and other aquatic environments, antibiotics may disturb the ecological balance of habitats and drive the spread of antimicrobial resistance (AMR) (Roberts, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Pharmaceuticals can be only partially metabolized during therapeutic use, resulting in the excretion and release of residual fractions into sewage, unaltered or in the form of metabolites, and may remain active in sewage treatment facilities for a long time [6,7,8]. Many studies have shown that wastewater treatment plants are not designed to eliminate these compounds, as such the main source of drug residues in the aquatic environment [6,7,9].…”
Section: Introductionmentioning
confidence: 99%